2021
DOI: 10.3389/fphar.2021.796628
|View full text |Cite
|
Sign up to set email alerts
|

Identification of miRNA and Their Regulatory Effects Induced by Total Flavonoids From Dracocephalum moldavica in the Treatment of Vascular Dementia

Abstract: Vascular dementia (VaD) is a general term used to describe difficulties in memory, reasoning, judgment, and planning caused by a reduced blood flow to the brain and consequent brain damage, in which microRNAs (miRNAs) are involved. Dracocephalum moldavica L. (D. moldavica) is traditionally used in the treatment of cardiovascular diseases as well as VaD, but the biomolecular mechanisms underlying its therapeutic effect are obscure. In the present study, the molecular mechanisms involved in the treatment of VaD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…With various pharmacological effects that include promoting blood circulation, removing blood stasis, clearing heat, and detoxifying, D. moldavica has a long history as a traditional Chinese medicine for treating cardiovascular and cerebrovascular diseases. In a previous study, we performed comprehensive miRNA profiling and constructed a compound-target gene-miRNA network of TFDM for cerebral ischemic treatment ( 30 ). We also showed that TFDM and its active compounds, namely tilianin, luteolin, and apigenin, protect against OGD injury by upregulating miR-3184-3p and downregulating miR-6875-5p in neuronal cells ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…With various pharmacological effects that include promoting blood circulation, removing blood stasis, clearing heat, and detoxifying, D. moldavica has a long history as a traditional Chinese medicine for treating cardiovascular and cerebrovascular diseases. In a previous study, we performed comprehensive miRNA profiling and constructed a compound-target gene-miRNA network of TFDM for cerebral ischemic treatment ( 30 ). We also showed that TFDM and its active compounds, namely tilianin, luteolin, and apigenin, protect against OGD injury by upregulating miR-3184-3p and downregulating miR-6875-5p in neuronal cells ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we performed comprehensive miRNA profiling and constructed a compound-target gene-miRNA network of TFDM for cerebral ischemic treatment ( 30 ). We also showed that TFDM and its active compounds, namely tilianin, luteolin, and apigenin, protect against OGD injury by upregulating miR-3184-3p and downregulating miR-6875-5p in neuronal cells ( 30 ). These findings provide a foundation that dysregulated miRNAs play a role in the therapeutic effect of TFDM and its active components against brain ischemia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditional Chinese medicine (TCM) has become one of the most important sources for exploring and developing modern medicines due to their application in treating various diseases for more than 5,000 years (Wang et al, 2018). Additionally, TCM can be further optimized to treat complex diseases due to its multicomponent, multi-target, and multi-pathway synergistic effects (Liu et al, 2021a;Cai et al, 2022a). Over the past few years, TCM has received increasing attention in treating NDs, and many NDs treatments of TCM origin are in different clinical trial stages (Shan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%